Teodulf z Orleanu, Poezje (wybór) - Gacia, Tadeusz (Vox Patrum, 2026)
This work is a Polish translation, preceded by an introduction, of seven selected poems by Theodulf of Orleans—four panegyric works dedicated to rulers, and three with Christian themes. These works demonstrate that Theodulf was a court poet, simultaneously a politician and promoter of the Carolingian Renaissance; a theologian fighting for dogmatic truth (the Filioque), but also a liturgist, mystic, and poet of nature. The translation is accompanied by essential, brief explanations.